The influence of servant leadership, job satisfaction, and intrinsic motivation on the performance of Aisyiyah kindergarten teachers - Mudrikah Mudrikah; Suyatno Suyatno; Achadi Budi Santosa (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Early childhood education plays a crucial role in shaping the foundation of children's development, making the quality of teacher performance a key factor in achieving optimal educational goals. Various factors can influence teacher performance, including the leadership style implemented by school leaders, the level of job satisfaction experienced by teachers, and the intrinsic motivation that drives them in carrying out their duties. This study aims to analyze the influence of servant leadership, job satisfaction, and intrinsic motivation on the performance of Aisyiyah kindergarten teachers in Banguntapan District. The research method employed is quantitative with a survey approach. The research sample consists of 37 teachers selected using a cluster random sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability. The data analysis technique used multiple linear regression to determine the extent to which the independent variables influence the dependent variable. The results indicate that servant leadership, job satisfaction, and intrinsic motivation have a positive and significant effect on teacher performance, both simultaneously and partially, with a significance value of p < 0.05. The implications of this study suggest that supportive leadership, high job satisfaction, and strong intrinsic motivation can enhance teacher performance in Aisyiyah kindergartens. Therefore, schools are advised to strengthen servant leadership strategies and create a conducive work environment to improve the quality of early childhood education.